2019
DOI: 10.1016/j.healthplace.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

“Being seen” at the clinic: Zambian and South African health worker reflections on the relationship between health facility spatial organisation and items and HIV stigma in 21 health facilities, the HPTN 071 (PopART) study

Abstract: Health workers in 21 government health facilities in Zambia and South Africa linked spatial organisation of HIV services and material items signifying HIV-status (for example, coloured client cards) to the risk of People Living with HIV (PLHIV) ‘being seen’ or identified by others. Demarcated HIV services, distinctive client flow and associated-items were considered especially distinguishing. Strategies to circumvent any resulting stigma mostly involved PLHIV avoiding and/or reducing contact with services and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 42 publications
4
37
0
Order By: Relevance
“…Including either of these variables in our models made little difference to the associations we saw between stigma and ART adherence. Hiding pills has been frequently reported in Zambia and South Africa [34] and, with strong unadjusted associations seen in this study, would be useful to explore in further work on stigma related to HIV treatment.…”
Section: Discussionmentioning
confidence: 84%
“…Including either of these variables in our models made little difference to the associations we saw between stigma and ART adherence. Hiding pills has been frequently reported in Zambia and South Africa [34] and, with strong unadjusted associations seen in this study, would be useful to explore in further work on stigma related to HIV treatment.…”
Section: Discussionmentioning
confidence: 84%
“…We hypothesize that HIV stigma may act as a barrier to PLHIV achieving viral suppression and that this effect may arise because stigma can reduce PLHIV being diagnosed quickly, slow the rate at which PLHIV start treatment, and/or impede antiretroviral medication adherence and attendance for follow-up ART collections and retention in care. Access to HIV testing has been constrained by stigma among men who have sex with men in high-income settings, 3 and among the general population in low-income settings, 4 , 5 because clients feel shame in accessing testing, anticipate being stigmatized when accessing services, 6 or want to avoid being associated with HIV. For similar reasons, stigma acts as a barrier to PLHIV accessing care in the United States, 7 among pregnant women who test positive in antenatal settings in Africa, 8 and more generally in low- and middle-income settings.…”
Section: Introductionmentioning
confidence: 99%
“…The same observation was made another test and treat trial in South Africa and Zambia [40] where people accessing HIV care in government facilities had to wait in a separate part of the health facility. The research team noted that 'being seen' at the clinic was a major barrier to care utilisation [41]. In our own study, despite this perceived barrier, some individuals actually preferred to visit the TasP trial clinics because they found the staff to be friendly, and the services to be quick and efficient.…”
Section: Discussionmentioning
confidence: 76%